MEMBUDAYAKAN JIWA LITERASI PADA PROSES PENDIDIKAN AGAMA HINDU TERHADAP GENERASI MUDA - Putu Subawa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Development in the field of education today, is an integral part of government effortsin order to improve and develop human resources in order to have high abilities or skills, moraland cultural values ??that are noble, intelligent, creative, independent and have strongcompetitiveness with the nation- other nations in the world. The development of science andtechnology in the millennium goals, the era of globalization and the information age today,demands all fields of life to be able to adjust to the level of progress itself. The nation's readinginterest is very worrying, whereas from reading, other language skills such as writing and speakingwill increase. Reading is a window to the world that makes people close to literary works,books, national character, and civilization. Literacy cannot be separated from language. A personis said to have literacy skills if he has acquired the basic ability of language, namely readingand writing. So, the basic meaning of literacy as literacy is the main door for the development ofthe meaning of literacy more broadly. And the method used to obtain literacy is through Education.Hinduism education is so important given, because it realizes that with religion it is hoped thatgenerations can become noble and responsible human beings. To further understand this, youare welcome to read carefully (literacy) and reflect on the statements listed in the following box.